A pilot study of active rehabilitation for adolescents who are slow to recover from sport‐related concussion. Issue 3 (3rd March 2015) - Gagnon, I.; Grilli, L.; Friedman, D.; Iverson, G. L.
Abstract : The purpose of this study was to examine the effectiveness of an active rehabilitation intervention for adolescents who are slow‐to‐recover after a sport‐related concussion. Ten adolescents (three girls and seven boys) seen at the Montreal Children's Hospital Concussion Clinic participated in this case series. Adolescents who were symptomatic more than 4 weeks after the injury were provided with an active rehabilitation intervention (M = 7.9 weeks following injury; range = 3.7 to 26.2 weeks). The rehabilitation program includes gradual, closely monitored light aerobic exercise, general coordination exercises, mental imagery, as well as reassurance, normalization of recovery, and stress/anxiety reduction strategies. The program continued until complete symptom resolution and readiness to begin stepwise return to activities. The primary outcome of the study was evolution of post‐concussion symptoms. Secondary outcomes included mood, energy, balance, and cognition. After the intervention, post‐concussion symptoms significantly decreased for the group of participants. They also had decreased fatigue and improved mood after 6 weeks of initiating the rehabilitation intervention. This case series shows that postconcussive symptoms and functioning in adolescents following sports‐related concussion can be improved after participation in an active rehabilitation intervention. The introduction of graded light intensity exercise in the post‐acute period following concussion is safe, feasible and appears to have a positive impact on adolescents' functioning.